IFRS 9 ‘Financial instruments’: Anticipated effects of the standard change at Kesko Group - Jääskeläinen, Antti (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
IFRS 9 Financial instruments presents the classification and measurement, the impairment and the hedge accounting requirements for accounting of financial instruments. The standard was set by the International Accounting Standards Board to replace IAS 39 Financial instruments: Recognition and Measurement on 1 January 2018. Hence, the long-criticized and complexly experienced requirements for accounting of financial instruments will undergo the most significant reform. This thesis addresses anticipated effects of IFRS 9, focusing on the challenges the new classification and measurement requirements bring forth in the case organization Kesko. This thesis was conducted as an action research, in which, a case study method was applied. The thesis was conducted with a twofold manner, which involved general analysis of IFRS 9 and further covered distinct ambitions related to the case organization. For the general part, empirical data was gathered by interviewing two IFRS experts from KPMG and PwC, while the interviews within the case organization constituted for the case study. Further, the literature on the IFRS 9 was such scant that the theoretical examination was merged with the IFRS experts’ quotations that also strived to contribute to the overall objective of reinforcing the body of research related to the subject. This thesis indicates that IFRS 9 will most fundamentally reform the impairment and the hedge accounting requirements of financial instruments. Regard to impairment, the changes are anticipated to increase the amount of loan-loss provisions, whereas the relaxed hedge accounting requirements are expected to encourage more companies to commence the application of hedge accounting. The thesis provides empirical support on that the term business model for managing financial assets, introduced in IFRS 9, is ably hard to comprehend and remains ambiguous. It goes on to argue that the most prominent issue in defining the business model for managing financial assets is the limits set in IFRS 9 for selling financial assets. In consideration of Kesko, this thesis finds that the key effects of IFRS 9 are anticipated to be the reshaping of the organization’s treasury policy and further examination of the possibility to apply hedge accounting for foreign exchange derivatives. What is more, the thesis presumes that complying the requirements of IFRS 9 Kesko will apply the hold to collect and sell model for managing financial assets in future.

IFRS 9 Rahoitusinstrumentit esittää luokittelun ja arvostamisen, luottotappioiden sekä suojauslaskennan säännökset rahoitusinstrumenttien tilinpäätöskäsittelyssä. Kansainvälinen tilinpäätösnormeja antava elin IASB sääti standardin korvaamaan IAS 39 Rahoitusinstrumentit: Kirjaaminen ja Arvostaminen -standardin 1.1.2018. Näin ollen jo kauan kritisoidut ja mutkikkaana koetut rahoitusinstrumenttien tilinpäätöskäsittelyn säännökset kokevat erittäin mittavan uudistuksen. Tämä tutkielma käsittelee IFRS 9:n ennakoituja vaikutuksia, keskittyen niihin haasteisiin, joita uudet luokittelun ja arvostamisen säännöt tuovat esiin case-organisaatio Keskossa. Tutkielma toteutettiin toimintatutkimuksena, jossa sovellettiin case-tutkimusmenetelmää. Tutkielman suoritus tapahtui kaksijakoisesti käsittäen yleistä analyysiä IFRS 9:stä sekä erillisiä tavoitteita case-organisaation suhteen. Yleisen osuuden empiirinen materiaali kerättiin haastattelemalla kahta IFRS-asiantuntijaa KPMG:ltä ja PwC:ltä, kun taas case-organisaatiossa toteutetut haastattelut muodostivat case-osuuden empiirisen materiaalin. Lisäksi, koska kirjallisuus IFRS 9:stä oli vähäistä, teoreettisessa tarkastelussa päätettiin liittää IFRS-asiantuntijoiden sitaatteja varsinaisen tekstin joukkoon. Tällä tavoin pyrittiin vahventamaan teoreettista tarkastelua sekä toteuttamaan tutkielman yleistä tavoitetta eli lisäämään tutkimusmateriaalia tutkimusaiheesta. Tutkielma osoittaa, että IFRS 9 tulee merkittävimmin uudistamaan luottotappioiden ja suojauslaskennan säännökset rahoitusinstrumenttien tilinpäätöskäsittelyssä. Luottotappioiden uuden käsittelytavan ennakoidaan aiheuttavan merkittäviä käyttöönottokustannuksia ja kasvattavan luottotappiovarausten määrää. Vastaavasti höllennettyjen suojauslaskentasäännöksien odotetaan rohkaisevan useampia yrityksiä aloittamaan suojauslaskennan. Tämä tutkielma tarjoaa empiiristä tukea sille, että IFRS 9:n esittelemä termi liiketoimintamalli rahoitusvarojen hallinnoissa on varsin haastava omaksua ja koetaan epäselvänä. Tutkielmassa myös perustellaan, että merkittävin kysymys määriteltäessä liiketoimintamallia rahoitusvarojen hallinnoissa on IFRS 9:ssä asetut rahoitusvarojen myyntien rajoitukset. Keskon suhteen tutkielmassa havaittiin, että standardin merkittävimpien vaikutusten ennakoidaan liittyvän organisaation rahoituspolitiikan mahdolliseen uudelleenmuotoiluun ja lisätutkimukseen mahdollisuudesta soveltaa suojauslaskentaa valuuttajohdannaisien osalta. Näiden lisäksi tutkielmassa todettiin, että Kesko tulee tulevaisuudessa IFRS 9:n mukaisesti soveltamaan liiketoimintamallia, jonka tavoitteena on sekä pitää rahoitusvaroja eräpäivään asti, että myydä niitä.